Philippines [videorecording (DVD)] - Mehta, Shilpa; Soldinger, Mark (Pilot Productions, 2009)
"Globe Trekker Shilpa Mehta visits a handful of the Philippines' 7100 islands, encountering great cultural, spiritual and geographical diversity on her way. The only Christian nation in South East Asia, the Philippines remain off the main beaten tourist track. Beginning her journey on the largest island of Luzon, Shilpa is treated by a faith healer, witnesses the Easter ritual of real life crucifixions, and visits the capital, Manila, before heading south to the beautiful island of Borocay. Shilpa travels on to Mindanao and finally to the more remote island of Palawan where she treks through the rainforest to meet the isolated Tau't Batu tribe"--Container.